A Brodie's abscess with soft tissue collection—complicating an already difficult diagnosis. Issue 1 (25th January 2018) - Gabbott, Ben; Faria, Giles; Lawson, George; Daly, Karen
Abstract: A healthy 14-year-old boy with a 3-month history of thigh pain and swelling is referred to a specialist centre with an uncertain diagnosis. After extensive tests and imaging a Brodie's abscess is diagnosed. The abscess is complicated by a fistula (cloaca) through the cortical bone of the femur, resulting in a large complex soft tissue collection. This is a presentation, we are unaware has been documented in any literature. After specialist multi-team combined management (Paediatric Trauma and Orthopaedic and Paediatric Infectious Diseases), the patient undergoes two surgical procedures, and extensive antibiotic cover. The patient makes a good recovery with no long lasting sequelae to date.